Application of hazardous serpentine rocks' extraction wastes in composites with glass waste and clay-sand mix to produce environmentally clean construction materials. (20th February 2020) - Mymrin, Vsévolod; Presotto, Petúla; Alekseev, Kirill; Avanci, Monica A.; Rolim, Paulo H.B.; Petukhov, Valerii; Taskin, Andrey; Gidarakos, Evangelos; Valouma, Aikaterini; Yu, Guoliang
Highlights: It was developed ceramics with 70 wt% of hazardous serpentinite extraction waste. Flexural strength of new ceramics (57 MPa) is 14 time higher than norms demands (4 MPa). Novel ceramics exhibit primarily glassy structures with some crystal inclusions. Obtained results permit bonding of all hazardous volatile "fibrils" of serpentine. Abstract: The objective of this research is to develop new ceramic materials using hazardous serpentine asbestos extraction dust waste (45–70 wt%), clay-sand mix (30–50%) and glass waste (0–5%). The raw materials and ceramics were characterized by XRD, XRF, SEM/EDS and LAMMA analyses. The ceramic bodies were formed by axial pressing, drying and sintering in an electric oven at temperatures of 950°, 1000°, 1050°, 1100°, 1150°, 1200°, 1250° and 1300 °C. The flexion resistance values of the ceramics varied in the range of 2.85–56.97 MPa, the water absorption rate ranged from 0.28 to 17.61% and linear shrinkage, between 5.80 and 11.66%. These values of the mechanical properties were achieved due to the chemical interaction of the raw materials and syntheses of mainly glass formations with inclusions of enstatite and forsterite. Using the present findings at the industrial level will provide an opportunity to solve a serious ecological problem of serpentine dust wastes contamination, to recover the ecological situation in the areas of serpentine mining and to avoid the accumulation of serpentine wastes.